A narrative inquiry concerning people of South Asian descent with type 2 diabetes and whether their diabetes impacts upon their relationships with family and friends. - Brown, Sinead (2012)
Introduction: Type 2 diabetes due to its increasing prevalence, cost, chronic nature and complications is an epidemic that the NHS must manage. Despite this, the literature relating to type 2 diabetes and social relationships in particular to the high risk population, South Asians, is limited and scarce. Literature Review: The literature, policies and evidence base surrounding South Asian diabetics and their social relationships was evaluated and analysed emphasising a central point that there is an area yet to be investigated leading to the formation of the research question: Do the symptoms, diagnosis, treatment and management of Type 2 diabetes impact upon the relationships of South Asian patients with their family and friends? Methodology: Narrative inquiry allows the researcher and the participants to form stories which examine the participant’s lives and the impact diabetes had upon their social relationships. The recruitment, procedure and data collection are discussed and semi-structured interviews are chosen as the method. The researcher developed a narrative analytical framework consisting of characters, settings, plot and causal relations which aims to answer the research question in depth. The issue of rigour and the ethical considerations are also discussed. Findings: 14 participants told their stories and through the analytical framework, diabetes was shown to have a powerful impact on relationships. Discussion: With this impact identified, the existing literature base surrounding it is analysed and evaluated. Limitations of the study are recognised and the reflections of the researcher are examined. Conclusion: The implications on nursing theory, practice and research are comprehensively evaluated and the research question is answered.